2006 IEEE LEOS Annual Meeting Conference Proceedings 2006
DOI: 10.1109/leos.2006.279133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of birefringence and eigen-axes orientation resulting from the interplay between initial and form birefringence in UV-illuminated fiber

Abstract: Birefringence and eigen-axes orientation are computed in UV-illuminated fibers with a high-order isoparametric vectorial finite element method. Form birefringence is included in the index profile of weakly birefringent fibers and various UV-beam orientations are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The study of the origin of photo-induced birefringence and its contributing factors in UVexposed optical fibers is important to determine the polarization behavior of in-fiber Bragg gratings [1][2][3][4][5][6][7][8]. Previous studies have identified three main contributions to photo-induced birefringence of gratings: orientation and state of polarization of the UV writing beam [1], transverse gradient in the UV-induced index change profile [2,3] and modification of glass stress profiles from the asymmetric glass densification in the photosensitive regions of the exposed fiber.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of the origin of photo-induced birefringence and its contributing factors in UVexposed optical fibers is important to determine the polarization behavior of in-fiber Bragg gratings [1][2][3][4][5][6][7][8]. Previous studies have identified three main contributions to photo-induced birefringence of gratings: orientation and state of polarization of the UV writing beam [1], transverse gradient in the UV-induced index change profile [2,3] and modification of glass stress profiles from the asymmetric glass densification in the photosensitive regions of the exposed fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified three main contributions to photo-induced birefringence of gratings: orientation and state of polarization of the UV writing beam [1], transverse gradient in the UV-induced index change profile [2,3] and modification of glass stress profiles from the asymmetric glass densification in the photosensitive regions of the exposed fiber. Other factors can also influence photo-induced birefringence such as fiber type [1,6], initial intrinsic fiber birefringence [7], hydrogenation [9] and laser writing beam wavelength and operation regime. Dependence of the induced birefringence on the polarization of the writing beam is attributed to the preferential bleaching of defects having their dipole moments aligned with the polarization of the UV writing beam [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations